ANALISIS MISKONSEPSI SISWA KELAS XII MAN KOTA CIMAHI PADA MATERI LIMIT FUNGSI ALJABAR - Wahyu Hidayat; Fikri Fauzi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Limits of functions are material in mathematics that is studied in schools as one of the foundations of calculus. Events that occur to students are that there is an incorrect understanding of the concept. Therefore, this study aims to identify high school students' misconceptions about the material limits of functions. The misconception indicators used include correlational misconceptions, theoretical misconceptions, systematic misconceptions, basic misconceptions, computational misconceptions, and language interpretation misconceptions. The method used was descriptive qualitative with the research subjects being 6 students of class XII MAN Cimahi City who were selected by purposive sampling. Data was collected through the results of essay questions which could identify misconceptions and interview students. Data were analyzed through three stages, namely first data reduction, namely classifying correct and incorrect student answers, secondly displaying data, namely incorrect student answers classified between misconceptions and blank answers, thirdly drawing conclusions/verification, namely by analyzing and describing the misconceptions that occur in students . The results showed that students had conceptual errors, including 33% in question number 1, did not experience conceptual errors in question number 2, 67% in question number 3, 67% in question number 4, 100% in question number 5, and 67% on question number 6.